Cross Cultural Communication Skills Development through Project Based Learning in International Language Education Programs - Dewi Nuryanti; Novita Kusumaning Tyas; Dina Destari (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study examines the effectiveness of Project Based Learning (PBL) in enhancing cross-cultural communication skills within international language education programs. As globalization increases, effective communication across cultures is essential, and language programs must equip students with these skills. PBL, a learner-centered instructional strategy, integrates real-world problems into the learning process, promoting student participation, collaboration, and critical thinking. The research found that students engaged in PBL showed significant improvements in communication competence, collaboration, and intercultural understanding compared to those in traditional lecture-based instruction. The study suggests that PBL not only enhances language proficiency but also fosters cultural awareness and empathy through projects involving cross-cultural collaboration and problem-solving. Furthermore, PBL offers a more effective platform for practicing language skills in real-world scenarios, as opposed to traditional methods focused on theoretical aspects. The findings demonstrate that PBL is particularly effective in international programs, where students from diverse cultural backgrounds work together to solve global issues, thus improving their ability to communicate and collaborate across cultures. The research concludes that integrating PBL into international language education programs significantly enhances students' cross-cultural communication skills. The study encourages educational institutions to adopt PBL and suggests further research on complementary strategies, including technology, virtual exchanges, and intercultural simulations.